IOT based visualization of weightage based static task scheduling algorithm in datacenter - M, Preethi; Jayavel, Kayalvizhi (International Journal of Engineering and Technology, 2018)
Cloud computing has raised majorly to provide everything as a service and also for scaling the resources and utilizing the resources in an effective way. This paper aims to propose a scheduling algorithm which allocates static tasks to the resources effectively without making any tasks starve for the resources for long time. In SJF algorithm, the shortest tasks will be executed initially, and the largest tasks will keep on starving for the resources to be allocated. The proposed algorithm handles such a situation effectively by adding the jobs under different weightage queues and then scheduling them in an SJF order. This gives priority to even largest job. In this paper a framework is proposed, which fetches data from Amazon SDB storage and the processing of data based on proposed algorithm occurs in a cloudsim and finally the results are visualized through an IOT mobile device. The comparison is also made for First Come First Serve (FCFS), which is a default scheduling algorithm and the proposed algorithm.